Health Monitoring System for Transformer by using Internet of Things (IoT) - Hanafi, Dirman; Aziz, Zarkhoni (International Journal of Electrical, Energy and Power System Engineering, 2022)
Transformer is an important device in electrical field that used to transfer electricity from one circuit to another with changing the voltage level. The transformer will be having a problem such as increasing in temperature and make a lot of noise. Typical transformer measurement system will take time for testing and less accurate. The aim of this project is to design the IoT system for monitoring and evaluate the performance of the transformer current, sound and temperature. The monitoring system using three types of sensors to sense the current, sound and temperature. ESP32 is being used to keep and process the data before sending to the Blynk application to show the value by using internet. Two different conditions are being tested to the transformer which are transformer without load and with load. Ammeter and ACS712 current sensor are used to get the current value. Besides, for temperature value used two equipment which are using thermometer and MLX90614 temperature sensor. The transformer sound obtained from the sound sensor. The data will be display in Blynk application. The result obtained show the health monitoring system for transformer by using Internet of Things is acceptable because has low error and save time to measure the parameters.